Complexation of Cm(III) and Eu(III) with 2,6-bis(5-(2,2-dimethylpropyl)-1H-pyrazol-3-yl)pyridine and 2-bromohexanoic acid studied by time-resolved laser fluorescence spectroscopy - Bremer, Antje; Geist, Andreas; Panak, Petra (Radiochimica acta, 2013)
Abstract The complexation of Cm(III) and Eu(III) with 2,6-bis(5-(2,2-dimethylpropyl)-1H-pyrazol-3-yl)pyridine (C5-BPP) and 2-bromohexanoic acid as lipophilic anion has been investigated by time-resolved laser fluorescence spectroscopy. Upon increasing ligand concentration three different Cm(III)-C5-BPP species with emission bands at 604.1 nm, 607.9 nm and 611.4 nm, respectively, are found and attributed to complexes with one, two and three C5-BPP molecules in the inner coordination sphere. Comparison with results of TRLFS experiments without 2-bromohexanoic acid shows that the C5-BPP ligand is able to completely displace the lipophilic anion from the inner coordination sphere, forming [Cm(C5-BPP)3]3+ complexes. This complex is also found in the organic phase of an extraction experiment performed with Cm(III), demonstrating that the lipophilic anion required for the extraction is not directly coordinated to the metal ion in the species formed during extraction. In case of Eu(III) the number of different species formed cannot be determined accurately. Nevertheless, the formation of the complex [Eu(C5-BPP)3]3+ in the presence of 2-bromohexanoic acid is confirmed.